Optimization of Thin-Walled Girders in Probabilistic Formulation - Gibczyńska, T.; Bereza, P. (Engineering Transactions, 1993)
This paper presents, in a probabilistic formulation, the optimization method of box and I-beams subjected to bending. Dimensions of the girder, material constants and the bending moment a.re random variables. The minimum area of the cross-section is assumed as the objective function. The conditions of strength and of local and global stability represent the constraints. The examples of calculations serve as a basis for comparative analysis of the results obtained and the results of deterministic optimization.